Statin/ezetimibe combination therapy vs statin monotherapy for carotid atherosclerotic plaque inflammation. Issue 10 (12th March 2021) - Oh, Minyoung; Kim, Hyunji; Shin, Eon Woo; Sung, Changhwan; Kim, Do-Hoon; Moon, Dae Hyuk; Lee, Ji Sung; Lee, Pil Hyung; Lee, Seung-Whan; Lee, Cheol Whan
Abstract : Abstract: It remains uncertain whether statin/ezetimibe combination therapy serves as a useful and equivalent alternative to statin monotherapy for reducing atherosclerotic plaque inflammation. The aim of the present study was to compare the effects of statin/ezetimibe combination therapy and statin monotherapy on carotid atherosclerotic plaque inflammation using 18 F-fluorodeoxyglucose ( 18 FDG) positron emission tomography (PET)/computed tomography (CT) imaging. Data were pooled from 2 clinical trials that used serial 18 FDG PET/CT examination to investigate the effects of cholesterol-lowering therapy on carotid atherosclerotic plaque inflammation. The primary outcome was the percent change in the target-to-background ratio (TBR) of the index vessel in the most diseased segment (MDS) at 6-month follow-up. Baseline characteristics were largely similar between the 2 groups. At the 6-month follow-up, the MDS TBR of the index vessel significantly decreased in both groups. The percent change in the MDS TBR of the index vessel (primary outcome) did not differ significantly between the 2 groups (−8.41 ± 15.9% vs −8.08 ± 17.0%, respectively, P  = .936). Likewise, the percent change in the whole vessel TBR of the index vessel did not differ significantly between the 2 groups. There were significant decreases in total and LDL cholesterol levels in both groups at follow-up ( P  < .001). There were no significant correlations between the percent changes in MDS TBR of the index vessel, changes in the lipid, and high-sensitive C-reactive protein levels. The reduction in carotid atherosclerotic plaque inflammation by statin/ezetimibe combination therapy was equivalent to that by the statin monotherapy.